Overseers of Upper Egypt: Addendum - Brovarski, Edward (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
Since my articles on the Overseers of Upper Egypt appeared in ZÄS 140 and ZÄS 141, I have become aware of three additional overseers. They are listed below.